2008
DOI: 10.4266/kjccm.2008.23.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Changes of the Brain-Dead Organ Donors: A 3-Year Experience

Abstract: Background: Success of transplantation is critically dependent upon the quality of the donor organ and optimal management. Recently, hormonal replacement therapy has been reported to result in rapid recovery of cardiac function and enable significantly more organs to be transplanted, while some other studies show conflicting results. The aim of this study is to comprehensively evaluate changes in basal circulating hormonal levels of the brain-dead organ donors.Methods: We reviewed the records of all brain-dead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…A marked drop in serum testosterone levels was detected 2 hours after injection of TNF into volunteer healthy men in one study [21]. A study including 23 brain-dead patients also demonstrated signi cantly low testosterone levels [22]. In the current study, testosterone levels were also signi cantly low in female patients on BD day.…”
Section: Discussionsupporting
confidence: 56%
“…A marked drop in serum testosterone levels was detected 2 hours after injection of TNF into volunteer healthy men in one study [21]. A study including 23 brain-dead patients also demonstrated signi cantly low testosterone levels [22]. In the current study, testosterone levels were also signi cantly low in female patients on BD day.…”
Section: Discussionsupporting
confidence: 56%